Science, ethics and politics: bioethics as a way for transforming scientific praxis - González Broquen, Ximena (Acta Bioethica, 2015)
Currently science is found in a paradoxical situation: the basis of scientific activity and the interrelations between science, technology, industry, society and State are strongly questioned and criticized, at the same time that the worldly idea of science as the only motor for human development prevails. There is where the idea of bioethics arises as trans-disciplinary knowledge —for, to and from life— as another way of doing and producing knowledge. In this article, the development of bioethics will be seen as an alternative to a type of knowledge, characterized in the first place as modern scientific paradigm, from which crisis, bioethics is born. This essay arises from a process of bibliographical review, exchange of ideas and analysis, during the course of ethics and science given as post-degree in Social Studies, in the Venezuelan Institute of Scientific Research.